Integrating generative AI tools in higher education - Emre, İlkim E. (American Journal of STEM Education, 2025)
This study focuses on the reflections from an academic perspective, integrating generative AI tools into teaching and research. In this regard, examples of how these tools are integrated and used, practical benefits, and ethical concerns are mentioned in the study. Drawing on personal experiences, the study explores topics such as academic integrity, AI literacy, and the challenges of adapting AI tools in an educational environment. A broader discussion of the future in an AI-driven world is presented, along with practical examples of AI adoption in higher education.